THE LITERATURE IN MENCHÚ’S TESTIMONIO AND THE TESTIMONIO IN ANZALDÚA’S LITERATURE: WORDS AS WEAPON - da Silva, Márcia Moura (Línguas & Letras, 2010)
<!--[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-GB;} p.MsoBodyText, li.MsoBodyText, div.MsoBodyText {margin:0cm; margin-bottom:.0001pt; line-height:200%; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:EN-US; font-weight:bold;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> Based on some of the definitions of testimonio as a genre this paper compares the works of Gloria Anzaldúa and Rigoberta Menchú, two authors who share an Indian heritage and who seem to function as mediators between the worlds of those they see as the oppressors and the oppressed. This paper looks directly at “Menchú’s Testimonio”, an oral account of the atrocities she experienced in Guatemala in the 1980’s made into a book by Elisabeth Burgos-Debray and some excerpts of the works by Anzaldúa, a writer and theorist who had to learn to live surrounded by prejudice against Mexican descendants living in the Texan-Mexican border. The main objectives of this paper are: a) identify the implied readers of their texts; and b) examine the role of literary elements in their narratives.